PENGARUH PERUBAHAN LAHAN PERTANIAN MENJADI NON PERTANIAN TERHADAP ASPEK SOSIAL EKONOMI MASYARAKAT - Sugiharto, Ferdi; Agustin, Nela (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
The transformation that occurs in the peri-urban area will cause changes in the morphological peri-urban area and affect changes in the form of agricultural land use and have an impact on changes in the socio-economic conditions of the people in the area. The purpose of this study was to determine the influence of changes in agricultural land to non-agriculture on the socio-economic aspects of the community in Jati Agung. This research uses a deductive approach. The data collection method used primary data from questionnaires and interviews, the secondary data collected from Landsat 8 satellite image and BPS South Lampung Regency in 2013-2020. The method of analysis uses the predominant peri-urban zone classification with urban or predominantly urban characteristics divided into Urban Frame Zones and Urban-rural Frame Zones, which have a percentage of agricultural land use less than 50%. Statistical linear regression method is used to see the effect of the transformation of agricultural land use into non-agriculture on the socio-economic aspects of the peoples. The results of statistical tests show that there is a disproportionate effect with a large effect of 29.5% on the total population, 7.6% on population density, 8.6% on Livelihoods and 20.2% on income.